Exports and regional development: a balance of the Kandir Law for Rio de Janeiro, Paraná and Minas Gerais (2019)
The study presents one of the most intense debates in the regional studies of the Brazilian economy: the effects of the Kandir law on the tax collection of the producer states of primary products destined for the world market. The high cycle of international prices of essential products, associated with the search for profits in the trade balance, started a clear process of reprimarization of the Brazilian economy and increased the dependence of some territories concerning the production of natural resources. Focusing on the case of three states of the federation (Minas Gerais, Rio de Janeiro, and Paraná), the study shows the losses that the three leading commodities producers have had, from the fiscal point of view, on the occasion of the Kandir law and the pursuit of greater national competitiveness in global markets.